Setting Objectives as the Basis of Coaching: Theoretical and Methodological Analysis of the Problem - Kulchytska, Anna (Psychological Prospects Journal, 2018)
The article is devoted to the problem of setting objectives as the basis of coaching. Contemporary human is constantly faced with the necessity of changing and choosing objectives, solving personality tasks associated with the crisis of values, finding self identity and comprehension of the lifeline. Often human does not reach the defined objective, or faces the problem of its setting and the choice of main life strategies. In this case, coaching is one of the types of practical assistance. The research has theoretical and methodological character. The detailed analysis of the setting objectives theories of leading domestic and foreign psychologists such as L. Vyhotskyi, J. Kelly, K. Levin, O. Leontiev, E. A. Locke, S. Rubinstein, T. Tytarenko, O. Tykhomyrova, Yu. Shvalb and others, has been carried out in presented work. As the result of the study, it has been determined that setting objectives acts as constructive factor of human activity, occupies one of the leading places both in the activity structure and directly in the process of its realization; setting objectives is the determining factor of personality becoming and is the key to successful life activity and subjective well-being; the single process of setting objectives are the lines of interrelations: «motive-objective», «objective-way», «objective-conditions», the central of which is the comparison of objectives and ways. On the basis of the results of theoretical and methodological analysis of the problem of setting objectives of a personality and comparing them with the concept of coaching, the author states that setting objectives is the leading process of the coaching approach in therapeutic activity of a psychologist. In order to increase efficiency in the coaching process, the author proposes to follow the basic stages of coaching. This is the objective setting, verification of the reality of the objective, formation of the ways to achieve the objective, formation of self-motivation, support and performance achievement.